Phenol degradation by Acinetobacter sp in the presence of heavy metals - Ahmad, SA; Shamaan, NA; Syed, MA; Dahalan, FA; Khalil, KA; Ab Rahman, NA; Shukor, MY (NATL SCIENCE FOUNDATION SRI LANKA, 2024)
Indexed by WOS/ Scopus